The use of near-Infrared spectroscopy in the sport-scientific context - Kozlova, S. (Journal of Neurology and Neurological Disorders, 2018)
The focus of this research is aimed specifically at the application of near-infrared spectroscopy (NIRS) in exercise and sport science. NIRS is able to monitor the performance of muscle and cerebral tissue and evaluate their role during physical activity. By monitoring tissue oxygenation, an NIRS device is useful in several areas, which may benefit from its applications. In the sport-scientific context, these tools would allow the follow-up of training performance progression over time, the identification of potential limitations, and an evaluation of the effects of therapeutic and rehabilitative interventions. The purpose of the present paper is to assess the current and potential utilization of the NIRS device in exercise and sport science in order to show the potential of this technique. We would like to introduce some trends evoking current interests and opinions in the field. This review article highlights recent studies related to the in vivo assessment of both cerebral and skeletal muscle tissue in the elite sport context using NIRS technology. After a brief description of the basic principles of NIRS measurement and NIRS technology, the work will examine studies carried out in professional athlete populations in a realistic sporting setting, as well as in some areas of application for laboratory use. Based on our findings, we would like to utilize NIRS to objectivize the rate of load and activation of CNS during exercise in professional athletes in future research projects. Among the findings from the presented studies in this review article, NIRS as a method for the functional evaluation of muscle and cerebral tissue oxidative metabolism has been successfully and reliably used in a variety of sporting contexts.